The Economic Impact Analysis of Earnings in Lahore, Pakistan - Fakhar, Sadia; Amber, Zaria (Asian Journal of Economic Modelling, 2018)
The rationale of this paper is to investigate the economic impact of gender differential and education on earnings in the city of Lahore, Punjab. It employs Ordinary Least Square (OLS) methodology by using “Pakistan Social and Living Standards Measurement” (PSLM) data of 2010-11. Different levels of education are positively linked with returns to education and experience. Educational returns are the highest at higher education level. Estimations also disclose gender differential in earnings because returns to education for women are lower than men in Lahore. Moreover, when the experience increases the educational returns also increase.